Tenuipalpid mites (Acari: Tenuipalpidae) of Olea europaea with a key to Brevipalpus from the genus Olea - Hatzinikolis, Ε.Ν. (ENTOMOLOGIA HELLENICA, 1986)
This paper deals with the tenuipalpid mites which are associated with olive trees and an account is given of their distribution, hosts, and bio-ecology. A key is provided to the species of Brevipalpus occurring on the genus Olea.